Examining Collaboration Within Child Welfare Multidisciplinary Teams: How Home-Based Therapists Respond to Conflict - Walsh, Matthew A. (2020)
Indiana University-Purdue University Indianapolis (IUPUI) === When the child welfare system becomes involved with a family in need of services it does so with the goal of concluding its involvement by finding a safe and permanent placement for the children, ideally with their parents. This challenging and complicated work often has many issues that need to be addressed before a successful closure can occur. To achieve this goal, multiple service providers with various backgrounds, degrees, and professions are tasked with working with each other and the family through a collaborative team called a multidisciplinary team (MDT). However, collaboration is not always guaranteed, and conflict can emerge as the team attempts to best serve the family. This conflict may emerge among professionals and between professionals and the family. Although the underlying factors of collaboration and conflict have been documented and studied, research on the process of resolving conflict when it occurs in MDTs is severely lacking in the literature. Furthermore, MDTs specific to the child welfare system also lack the focus they deserve within the child welfare literature. This grounded theory study addresses the gap by focusing on child welfare MDTs and specifically on home-based therapists (N=20) to determine not only their perceptions of facilitators and barriers to collaboration but also the process that they and their fellow service providers engage in when addressing and resolving conflict. In conducting this qualitative study, this researcher used grounded theory to construct a theory outlining the processes that home-based therapists utilize to resolve conflict within MDTs, starting with the emergence of the conflict and detailing the decision making process through the team’s reaction and the ultimate decision or final result. In the future, these findings could be used to aid and train other MDT members as they face their own conflicts with the hope that a more efficient conflict resolution process will lead to a more effective MDT that keeps its focus on the family and provides the needed treatment and services in a timely manner.